Breast screening: the facts—or maybe not. (27th January 2009) - Gøtzsche, Peter C; Hartling, Ole J; Nielsen, Margrethe; Brodersen, John; Jørgensen, Karsten Juhl
Abstract : Peter Gøtzsche and colleagues argue that women are still not given enough, nor correct, information about the harms of screening